2015
DOI: 10.1007/s11085-015-9563-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Resistance to Steam Oxidation of Aluminide-Coated AISI 304 and AISI 316 Steel Produced by Chemical Vapor Deposition in a Fluidized Bed Reactor

Abstract: Various techniques have been used to deposit aluminium on ferritic and austenitic steels to increase their oxidation resistance. An aluminide coating was deposited on AISI 304 and AISI 316 stainless steels by chemical vapor deposition at 580°C for 1.5 h in a fluidized bed reactor. The as-deposited samples were treated at 750°C in Ar atmosphere for 2 h. Scanning electron microscopy/energy-dispersive X-ray spectroscopy and X-ray diffractometry were used to study morphology and composition. Deposition results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…As we know, the aluminides exhibit high stability in the presence of steam; they are good because they act as thermal barriers to hinder ionic mobility and they increase the potential energy barrier for diffusion. In addition, a film thickens as a consequence of its resistivity . Thus, the resistance of iron aluminides to chemical degradation in a number of high‐temperature environments correlates with the ability of these alloys to quickly form and maintain the protective Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As we know, the aluminides exhibit high stability in the presence of steam; they are good because they act as thermal barriers to hinder ionic mobility and they increase the potential energy barrier for diffusion. In addition, a film thickens as a consequence of its resistivity . Thus, the resistance of iron aluminides to chemical degradation in a number of high‐temperature environments correlates with the ability of these alloys to quickly form and maintain the protective Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum‐silicon coating was deposited using the CVD‐FBR system at 580 °C for 2 h. CVD‐FBR characteristics for this research have been reported in previous works . The bed was a mixture of 100 wt% (Al + Si + Al 2 O 3 ) powder (99.9% pure, particle size under 400 μm diameter).…”
Section: Experimental Partmentioning
confidence: 99%
See 3 more Smart Citations